Necesidad de reformar el art. 4 de la ley contra la violencia a la mujer y la familia para incorporar el tipo de violencia patrimonial . - Criollo Agila, Soraya Emperatriz (2015)
Violence is a social economic phenomenon in the world of transcendental civil social order, a determinant of the social, political, and it is a global social scourge that affects substantial magnitudes basic legal rights of human beings that have weakened in different areas of the person's psychological, physical, sexual and economic environment. According to the United Nations, 6 out of 10 women in Ecuador suffer from violence, while 1 in 5 women in the world is a victim of rape or attempted rape. In Ecuador, 61% of women have experienced some form of violence. 1 in 4 women has experienced sexual violence. However, psychological violence is the most recurrent form of gender violence in the country, with 53.9 % of cases. And el76 % of women have been raped by their partner or ex-partner, most of the time, the crime or abuse is not committed on the street or at work, but on the contrary , it happens behind closed doors , in the private space: the house, privacy and home. These are the main data conclude the First National Survey of Family Relations and Domestic Violence against Women. According to a report by Amnesty International, at least 1 in 3 women has been beaten, have forced the sex or has suffered some other kind of abuse. UNIVERSIDAD NACIONAL DE LOJA MODALIDAD DE ESTUDIOS A DISTANCIA The statistics are indisputable referenced scenario of gender inequality, existence of degrading behaviors that affect directly or indirectly the integrity of the family and of women in particular, who continues to experience discrimination in different areas of public and private participation; While the evolution of public policy in the prevention of violence in all its forms has been positive, gradually have generated projects through interagency cooperation aimed at strengthening from the various priorities the protection of the rights of individuals, prevention affirmative actions have led to greater recognition of the prerogatives of the people and therefore we can say that there are significant advances in respect for and protection of personal integrity that just includes the right to have all people to live in an environment free from violence in all its forms. But domestic violence and gender is a conflict of structural order that requires continuous processes of awareness, training and cooperation to build new patterns of behavior and cultural patterns that ensure gender equality, understood as the right of men and women to participate and act on equal conditions in political, economic and family processes.